An Assessment of the Effectiveness of Alternative Dispute Resolution Methods - Sauden, Anup; Chhetri, Surya (Journal of Productive Discourse, 2023)
This study assesses the effectiveness of Alternative Dispute Resolution (ADR) practices in projects run under the Department of Roads of Nepal government. Secondary data from case studies and primary data from questionnaire and key informant interviews are analysed in view of the decisions regarding the use of ADR in settlement of road project cases. The research uses a descriptive method in the assessment. Out of eight (8) projects, disputes related to four (4) were settled by litigation based on ADR (Adjudication and Arbitration) decision, one was sent for the reformation of arbitration by court/litigation and three (3) were awarded by ADR (Arbitration) but remained pending in the settlement process by litigation till 14 May 2022. Negotiation (i.e. amicable settlement) is the most applied ADR to resolve the disputes followed by Conciliation, Mediation and Adjudication. Arbitration is used as the last stage of ADR due to its high legal value in spite of the high time and cost. The study is significant for professionals to overcome the identified causes effectively to create zero-dispute projects by handling the issues in real time.